Simplicity Denervation System for Pulmonary Artery Denervation in Patients with Residual Pulmonary Hypertension after Pulmonary Thromboembolism and Surgical Thrombectomy - Rudenko, B.; Shanoyan, A.; Drapkina, O.; Gavrilova, N.; Beregovskaya, S.; Akhadova, A.; Feshchenko, D.; Shukurov, F.; Vlasov, V.; Boytsov, S.; Dzemeshkevich, S.; Frolova, Yu.; et al. (Cardiology and Cardiovascular Medicine, 2017)
Purpose: To study the safety and effectiveness of simplicity denervation system in lowering pulmonary artery pressure in patients with pulmonary hypertension after pulmonary thromboembolism and surgical thrombectomy. Methods: We analyzed the 3-months results of 12 procedures of pulmonary artery denervation with the simplicity denervation system. The primary endpoints were the change of pulmonary artery pressure and 6 minutes walking test at 3 months follow-up. Results: The procedure of pulmonary artery denervation was performed at the ostium of the right and left pulmonary arteries using the electrode from Simplicity denervation system. Using the coronary guiding technique, the tip of electrode was placed at the ostium of the pulmonary artery, then the radio frequency energy was applied (temperature >50°C, energy = 12 W, and time = 120), rotating the tip with pace of 2 mm at the ostium of each pulmonary artery. The proper position of the electrode (tight contact with the vessel wall) was checked automatically by resistance monitoring and manual tracking. At 3 months follow-up the pulmonary artery pressure decreased from 58 ± 6 to 33 ± 4 mm Hg (p < 0.01) and improvement of the 6 minutes walking test from 321 ± 19 m to 487 ± 29 m (p < 0.01) was observed. Conclusion: The simplicity denervation system is proven to be safe and effective for pulmonary artery denervation. Further randomized study is needed to confirm the clinical benefit of this procedure in patients with pulmonary hypertension.